Membangun Teologi Tubuh Dari Bawah Belajar Dari Pengalaman Olah Tubuh Tari Lengger - Robertus Suraji (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2018)
The word theology comes from the Greek word theos which means God, and logos which means words. Thus theology means words or knowledge about God. The body can say or show or remind something about God as the ruler of human body and life. Reflection on body can bring people to the knowledge of God. The experience of lengger dancers working on the body makes them believe in the existence of God as the origin of his body, even though they did not dare to expressly mention the name of Allah behind all of these experiences. Body work experience gives them confidence that there is something behind this visible physical body. However, the human body is not only owned by a person, but has become a sign system of community culture. The body no longer only has the meaning of itself, but also must obey the general norms that apply in the society where a person lives. The meaning of the lengger dancer's body is very dependent on the interpretation of the surrounding community, the majority of whom are Muslim. While Islam teaches that the body, especially the female body, must be protected because it has the potential to bring sin. However, the community's interpretation of the body is not monolithic. The situation and culture in which they live determines the interpretation of how to treat the female body. This is where there is often a value tension between Islamic teachings and traditional values.